Unravelling the unusual: Enterococcus faecium in aspiration pneumonia complicated with lung abscess in a severely comorbid patient - Asokan, Devi; Bawankar, Neha Sunil; Khadse, Ravindra R.; Bhise, Swati M. (International Journal of Research in Medical Sciences, 2024)
Aspiration pneumonia is a common respiratory infection that can lead to complications, including lung abscess. While typical causative agents include P. aeruginosa, K. pneumoniae, and S. aureus, atypical agents must also be considered, especially in comorbid or elderly populations. This case report presents a rare instance of aspiration pneumonia caused by E. faecium that developed into a lung abscess in a patient with multiple comorbidities. The patient's medical history included left-sided hemiparesis, hypertension, and type-2 diabetes mellitus, as well as a thirty-year history of smoking and alcoholism. Radiological evaluation revealed a rounded opacity with an air-fluid level in the left lower zone, indicating a lung abscess. Microbiological evaluation confirmed the presence of Enterococcus spp. The case highlights the importance of considering atypical pathogens in aspiration pneumonia and the potential for severe complications in severely comorbid patients.